Estamos em pandemia, mas não perdemos a alegria - Carraro , Adriana Pohl; Pereira , Ana Carolina Ávila; Araújo , Angela Machado Gomes; Silva , Elenice Aparecida da; Ferrari , Fabiana; Atayde , Joselda de Oliveira; Araujo, Jucelio Alexandre; Avila , Lucia Helena de Souza; Acrisio, Marcos José; Freitas , Marcos Rodrigues de; Almeida , Maria Luiza de Almeida Dias; Fernandes , Rosa Maria; et al. (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2023)
>>> ver pdf